Long‐term clinical outcomes after unprotected left main coronary artery stenting in an all‐comers patient population. Issue 4 (5th March 2013) - Ali, Mohammed; Hanley, Alan; McAdam, Brendan; O'Hanlon, Rory; Gumbrielle, Thomas; Sheahan, Richard; Foley, David P.
<x xml:space="preserve">Abstract</x> Background The goal of treating patients with coronary artery disease is to improve survival and relieve symptoms. Several studies have compared the safety and efficacy of left main coronary artery (LMCA) stenting and coronary‐artery bypass grafting in case control and randomized trials. Objective In this study we present the long term outcome of stenting unprotected LMCA stenosis in day to day practice in unselected patients. Methods One hundred and fifty eight patients were prospectively recruited with symptomatic unprotected LMCA stenosis undergoing percutaneous coronary intervention (PCI). Using the euroSCORE, each patient's surgical mortality risk was estimated. Study end‐points were any major adverse cardiac event (MACE) defined as cardiac death, nonfatal myocardial infarction, or target lesion revascularization at follow‐up with either CABG or repeat PCI. Results The mean follow‐up was 54 ± 25 months. The mean euroSCORE was 10.6 ± 13.4 (0.9–71) and the mean SYNTAX score was 39.6 ± 10.7 (10–65). The MACE rate was 11.4% at a mean follow up of 54 months. Six (3.8%) patients suffered postprocedure myocardial infarction. There were 24 (15%) deaths of which 12 were cardiac (mean euroSCORE 21.6 ± 5.5 P < 0.001). Repeat angiography was performed in 88 (55.7%) patients. Seven (4.4%) patients had in‐stent restenosis; three occurred in BMS (P = 0.06). Two patients underwent revascularization with CABG and five had successful repeat PCI. Conclusion In this on‐going registry of high risk patients with LMCA stenosis, stenting was found to be safe and clinically effective in maintaining event‐free survival.© 2013 Wiley Periodicals, Inc.